Organic transition schemes for a Morris county Kansas grain farm - Moore, Russell T. (Kansas State University, 2008)
Profitability is a primary economic motivator for a farm to remain in business. As conventional crop farming endures rising fertilizer and chemical costs, small farmers that raise grains must look towards innovative cropping practices that are economically affordable or depart the business. As small farmers evaluate other cropping prospects, organic cropping systems and the availability of organic price premiums should be considered as an alternative in meeting farm profitability goals. This study compared the economic return per acre of converting to an organic cropping system from a conventional system against the conventional crop enterprise of the same crop mix. A simulation model was created using assumed organic yield data, actual organic prices, historical conventional yield data and historical conventional prices to determine the economic return. An initial simulation was run, ignoring the three-year transitional period that farms must undergo with no synthetic inputs to become certified organic, to determine if organic cropping systems using organic price premiums on the 600-acre farm would be competitive with conventional production. The simulation showed that organic production is economically competitive with conventional production. Previous studies and personal interviews indicated that the three-year transitional period could easily cause the farm economic loss, since conventional inputs cannot be used and organic premiums cannot be obtained for crops sold. Therefore, three different conversion schemes were simulated to find which one would cause the farm the least economic damage: converting the entire farm to organic production at once, converting 20% of the farm's tillable acres to organic production annually and converting 10% of the farm's tillable acres to organic production annually. All three of the proposed transition schedules revealed economic loss to the farm at some point during their transition periods. The only scheme that showed no average loss was the existing conventional system. However, after complete transition, the three transition schemes showed higher profitability than the conventional cropping system. The downside was that this took a minimum of 13 years to accomplish. The only scheme that did not cause the farm's cumulative present value to drop into negative numbers was the 10% per year transition rate.
Keywords: Organic farming; whole farm analysis; transition; grain; family farm; crop budget; Economics, Agricultural (0503)